1981
DOI: 10.2172/5835490
|View full text |Cite
|
Sign up to set email alerts
|

Oil shale commercialization study

Abstract: Ninety f o u r p o s s i b l e o i l s h a l e s e c t i o n s i n s o u t h e r n I d a h o were l o c a t e d and c h e m i c a l l y a n a l y z e d. S i x t y-t w o o f t h e s e s h a l e s show good promise o f. p o s s i b 1 e o i l and p r o b a b l e g a s p o t e n t i a l .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…the classical model corresponds to T S / T T B + m, while the extreme inhomogeneous or dilution only models are represented by T,/TTB -+ 0. This argument is consistent with the good agreement reported by Baker et al between droplet spectra observed in cumulus by Warner (1969) which classical theory could not explainand ones calculated on the basis of T s / T T B + 0.…”
Section: The Ratios T~b / T T B and T T B / T supporting
confidence: 92%
See 3 more Smart Citations
“…the classical model corresponds to T S / T T B + m, while the extreme inhomogeneous or dilution only models are represented by T,/TTB -+ 0. This argument is consistent with the good agreement reported by Baker et al between droplet spectra observed in cumulus by Warner (1969) which classical theory could not explainand ones calculated on the basis of T s / T T B + 0.…”
Section: The Ratios T~b / T T B and T T B / T supporting
confidence: 92%
“…Recent work (Baker and Latham 1979;Baker et al 1980;Telford and Chai 1980;Telford and Wagner 1981) has indicated that the non-uniform manner with which the environmental air mixes with the cloud can give rise to fluctuations in supersaturationnot,linked to changes in updraught speedwhich cause spectral broadening. A small fraction of the droplets move through the condensate spectrum to the coalescence stage of growth up to several times faster than predicted by classical descriptions of the entrainment process (for example, Warner (1973), Mason and Jonas (1974), Lee and Pruppacher (1977)), in which the mixing between environmental and cloudy air at any level was assumed to be instantaneous and uniform. The droplet spectra predicted by Baker et al agreed well with those measured in cumulus by Warner (1969).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Bohr and Mottelson [1] shown that gamma-ground M1 transitions can't be explained via K=2 mixing alone, but theey require, in addition, the existence of Δk=1 mixing with higher lying K=1 band. Warner [10] shows that the difference in the strength of the pairing for neutron and proton gives rise to different neutron and proton deformations which in term of generate M1 transition.…”
Section: Introductionmentioning
confidence: 99%